Compton-driven beam formation and magnetization via plasma microinstabilities. (25th June 2021) - Martinez, Bertrand; Grismayer, Thomas; Silva, Luís O.
Abstract : Compton scattering of gamma rays propagating in a pair plasma can drive the formation of a relativistic electron positron beam. This process is scrutinized theoretically and numerically via particle-in-cell simulations. In addition, we determine in which conditions the beam can prompt a beam-plasma instability and convert its kinetic energy into magnetic energy. We argue that such conditions can be met at the photosphere radius of bright gamma-ray bursts.